Glossary of Chinese Islamic terms - Wang, Jianping (Curzon Press, 2001)
The most comprehensive glossary to date of Hui Muslim terms and the first to fully match the Chinese term (stated in Chinese script and pinyin) to its Arabic or Persian counterpart (stated in Arabic script with Latin transcription).